2002
DOI: 10.1161/hc0602.103673
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cell Vascular Endothelial Growth Factor Gene Transfer for Vascular Regeneration

Abstract: Background — Previous studies have established that bone marrow–derived endothelial progenitor cells (EPCs) are present in the systemic circulation. In the current study, we investigated the hypothesis that gene transfer can be used to achieve phenotypic modulation of EPCs. Methods and Results — … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
372
2
7

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(390 citation statements)
references
References 42 publications
9
372
2
7
Order By: Relevance
“…Already these variations in the coating strategy may have an influence on the results obtained by cell culture with respect to cell number, cell phenotype, and cell function. Another important factor regulating the fate of the plated cells is the cell culture media ranging from EBM-2 (23-25), medium-199 (22,26,27), to x-vivo-20 (28) as basal media, and 20% fetal calf serum (1), brain extract (1,26), to commercial available single quots of VEGF, insulin-like growth factor (IGF), basic fibroblast growth factor (23,25) as supplements. An identification criteria often used for EPCs in the culture of MNCs for 4 or 7 days is the double-positive staining of EPCs for endothelial-specific lectin (e.g., Ulex europaeus agglutini-1) and Dil-labeled acetylated low-density lipoproteins (Ac-LDL) (26,29,30).…”
Section: Cell Culturementioning
confidence: 99%
“…Already these variations in the coating strategy may have an influence on the results obtained by cell culture with respect to cell number, cell phenotype, and cell function. Another important factor regulating the fate of the plated cells is the cell culture media ranging from EBM-2 (23-25), medium-199 (22,26,27), to x-vivo-20 (28) as basal media, and 20% fetal calf serum (1), brain extract (1,26), to commercial available single quots of VEGF, insulin-like growth factor (IGF), basic fibroblast growth factor (23,25) as supplements. An identification criteria often used for EPCs in the culture of MNCs for 4 or 7 days is the double-positive staining of EPCs for endothelial-specific lectin (e.g., Ulex europaeus agglutini-1) and Dil-labeled acetylated low-density lipoproteins (Ac-LDL) (26,29,30).…”
Section: Cell Culturementioning
confidence: 99%
“…It has been reported that marrow-derived endothelial progenitor cells contribute to adult vasculogenesis (Tamura et al, 2004) and tumour angiogenesis (Rafii et al, 2002;Peters et al, 2005) by circulating through the vascular system and incorporating into the wall of newly formed vessels (Marchetti et al, 2002;Rafii and Lyden, 2003). Evidence that vasculogenesis is involved in neovascularisation has been found in studies on tumour vessels (Reyes et al, 2002), experimental retinopathy (Grant et al, 2002;Tomita et al, 2004;Butler et al, 2005), myocardial ischaemia (Kocher et al, 2001(Kocher et al, , 2006Botta et al, 2004), wound healing Crisa et al, 1999), and hindlimb ischaemia Kalka et al, 2000;Iwaguro et al, 2002). An important question that remains unanswered by the literature is whether circulating endothelial progenitor cells per se or their differentiated progeny are incorporated into the vascular wall .…”
mentioning
confidence: 99%
“…59 In an animal model of experimentally induced limb ischemia, Iwaguro el al. 60 showed that administration of EPC transduced with adenovirus encoding VEGF improved neovascularization and blood flow recovery and reduced amputation rate. In this study, EPC-mediated adenoviral VEGF gene therapy was able to achieve curative effects despite the use of subtherapeutical EPC doses.…”
Section: Bone Marrow-derived Endothelial Progenitor Cells As Carriersmentioning
confidence: 99%
“…In this study, EPC-mediated adenoviral VEGF gene therapy was able to achieve curative effects despite the use of subtherapeutical EPC doses. 60 Thus, combined EPC and gene therapy is an option to address the problem of limitations in the number of EPC that can be obtained for clinical applications.…”
Section: Bone Marrow-derived Endothelial Progenitor Cells As Carriersmentioning
confidence: 99%